2020
DOI: 10.1002/jcpy.1179
|View full text |Cite
|
Sign up to set email alerts
|

Numbers and Units Affect Goal Pursuit Organization and Motivation

Abstract: Goals are one of the most ubiquitous drivers of behavior. Despite the wealth of research on goal pursuit, less is known about how individuals organize their goal pursuit in the first place. This manuscript represents one of the first studies to provide insight into quantitative goal organization, proposing that the unit/numerical value in which a goal is described influences goal pursuit organization. Specifying a superordinate goal in units with larger numbers (e.g., studying for an examination for 120 min pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Participants in the low (vs. high) self‐concept clarity condition showed greater interest in cosmetic procedures ( M low = 2.53, SD = 1.76 vs. M high = 2.12, SD = 1.67; t [353] = 2.25, p = 0.025, d = 0.24). On closer inspection, we found that interest in cosmetic procedures was positively skewed (skewness = 1.15, which was greater the threshold for high skewness of 1; Lembregts & Pena‐Marin, 2021): 38% of participants in the low self‐concept clarity condition and 54% of participants in the high self‐concept clarity condition indicated zero interest in cosmetic procedures (i.e., interest in cosmetic procedures index = 1; χ 2 = 8.07, p = 0.004). Although we did not preregister transforming the dependent variable, to achieve the normality assumption in linear regression for subsequent mediation analysis, we log transformed interest in cosmetic procedures (Cohen et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
“…Participants in the low (vs. high) self‐concept clarity condition showed greater interest in cosmetic procedures ( M low = 2.53, SD = 1.76 vs. M high = 2.12, SD = 1.67; t [353] = 2.25, p = 0.025, d = 0.24). On closer inspection, we found that interest in cosmetic procedures was positively skewed (skewness = 1.15, which was greater the threshold for high skewness of 1; Lembregts & Pena‐Marin, 2021): 38% of participants in the low self‐concept clarity condition and 54% of participants in the high self‐concept clarity condition indicated zero interest in cosmetic procedures (i.e., interest in cosmetic procedures index = 1; χ 2 = 8.07, p = 0.004). Although we did not preregister transforming the dependent variable, to achieve the normality assumption in linear regression for subsequent mediation analysis, we log transformed interest in cosmetic procedures (Cohen et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
“…For example, consumers (and researchers) may see adopting a vegetarian or vegan lifestyle as a big challenge and consequently fail to reduce their meat consumption. However, the literature on consumer goals (Fishbach & Dhar, 2006;Gal & Mcshane, 2012;Lembregts & Pena-Marin, 2021) suggests that unpacking such an intimidating task into smaller steps would help with this starting problem (e.g., by reducing meat consumption to once or twice a week or shifting to chicken products).…”
Section: Focus On Consumer-relevant Systemic Factorsmentioning
confidence: 99%